Adjunctive use of p16 immunohistochemistry for optimizing management of CIN lesions in a high‐risk human papillomavirus‐positive population - Renée M. F. Ebisch; L. Lucia Rijstenberg; Gilda Ghazi Soltani; Judith van derHorst; Judith E. M. Vedder; Meyke Hermsen; Remko P. Bosgraaf; Leon F. A. G. Massuger; Chris J. L. M. Meijer; Daniëlle A. M. Heideman; Folkert J. vanKemenade; Willem J. G. Melchers; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Immunostaining with p16INK4a (p16), a tumor‐suppressor surrogate protein biomarker for high‐risk human papillomavirus (hrHPV) oncogenic activity, may complement standard hematoxylin and eosin (H&E) histology review, and provide more objective criteria to support the cervical intraepithelial neoplasia (CIN) diagnosis. With this study we assessed the impact of p16 immunohistochemistry on CIN grading in an hrHPV‐based screening setting. Material and methods In this post‐hoc analysis, 326 histology follow‐up samples from a group of hrHPV‐positive women were stained with p16 immunohistochemistry. All H&E samples were centrally revised. The pathologists reported their level of confidence in classifying the CIN lesion. Results Combining H&E and p16 staining resulted in a change of diagnosis in 27.3% (n = 89) of cases compared with the revised H&E samples, with a decrease of 34.5% (n = 18) in CIN1 and 22.7% (n = 15) in CIN2 classifications, and an increase of 18.3% (n = 19) in no CIN and 20.7% (n = 19) in CIN3 diagnoses. The level of confidence in CIN grading by the pathologist increased with adjunctive use of p16 immunohistochemistry to standard H&E. Conclusions This study shows that adjunctive use of p16 immunohistochemistry to H&E morphology reduces the number of CIN1 and CIN2 classifications with a proportional increase in no CIN and CIN3 diagnoses, compared with standard H&E‐based CIN diagnosis alone. The pathologists felt more confident in classifying the material with H&E and p16 immunohistochemistry than by using H&E alone, particularly during assessment of small biopsies. Adjunctive use of p16 immunohistochemistry to standard H&E assessment of CIN would be valuable for the diagnostic accuracy, thereby optimizing CIN management and possibly decreasing overtreatment.